1997
DOI: 10.1073/pnas.94.5.2013
|View full text |Cite
|
Sign up to set email alerts
|

d -aspartate localizations imply neuronal and neuroendocrine roles

Abstract: Though L-amino acids predominate in living organisms, substantial levels of free D-serine and D-aspartate occur in mammals, especially in nervous and endocrine tissues. Using an antibody specific for glutaraldehyde-fixed D-aspartate, we have localized D-aspartate in rat tissues. In the brain we observe discrete neuronal localizations of Daspartate, especially in the external plexiform layer of the olfactory bulb, hypothalamic supraoptic and paraventricular nuclei, the medial habenula, and certain brainstem nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(184 citation statements)
references
References 35 publications
7
177
0
Order By: Relevance
“…If DR physiologically forms D-aspartate, then the enzyme and its product should have similar localizations. D-aspartate is highly concentrated in the supraoptic and paraventricular hypothalamic nuclei, whose axons terminate in the posterior pituitary (19). Our immunohistochemical studies revealed similarly high densities of DR in the paraventricular and supraoptic nuclei (Fig.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…If DR physiologically forms D-aspartate, then the enzyme and its product should have similar localizations. D-aspartate is highly concentrated in the supraoptic and paraventricular hypothalamic nuclei, whose axons terminate in the posterior pituitary (19). Our immunohistochemical studies revealed similarly high densities of DR in the paraventricular and supraoptic nuclei (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…The free-floating sections were quenched with 0.1% H 2 O 2 in methanol/PBS, blocked with 4% normal goat serum and 0.2% Triton X-100 in TBS (blocking buffer), and incubated with DR antibody, diluted 1:700 in blocking buffer, overnight at 4°C. For immunohistochemistry, DR antibody works optimally D-Aspartate immunohistochemistry was conducted as described previously (19). C57BL/6 mice were perfused with 5% glutaraldehyde/0.5% paraformaldehyde at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Although the function of D-aspartate in mammalian brain is still matter of debate, mounting evidence has indicated that this D-amino acid may act as a putative neuromodulator of the glutamatergic system (Schell et al, 1997;Errico et al, 2008a). Here we examined the hypothesis that elevation of D-aspartate concentrations in adult mice might unveil its central influence in behaviors and electrophysiological paradigms associated with NMDAR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Another D-amino acid, named D-aspartate, occurs in the mammalian brain. D-Aspartate levels are high in the embryonic phase and dramatically decrease during postnatal life, in concomitance with increased expression of D-aspartate oxidase (DDO), the enzyme responsible for its deg- radation (Schell et al, 1997;Errico et al, 2006;Huang et al, 2006). In contrast to D-serine, now well characterized for its implication in NMDAR-dependent functions, the role of D-aspartate in the CNS remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…12 Free D-aspartate (D-Asp) is present in markedly high amounts in the embryonic brain of mammals. After birth, the endogenous levels of this atypical amino acid rapidly decrease, [13][14][15][16] due to the onset of the D-aspartate oxidase (DDO) activity. 17 Recent evidence has shown that D-Asp activates NMDARs through the binding to the glutamate site of GluN2 subunits.…”
Section: Introductionmentioning
confidence: 99%